Surface modification of silica particles with gold nanoparticles as an augmentation of gold nanoparticle mediated laser perforation - Kalies, Stefan (Optical Society of America, 2014)
Gold nanoparticle mediated (GNOME) laser transfection/perforation fulfills the demands of a reliable transfection technique. It provides efficient delivery and has a negligible impact on cell viability. Furthermore, it reaches high-throughput applicability. However, currently only large gold particles (> 80 nm) allow successful GNOME laser perforation, probably due to insufficient sedimentation of smaller gold nanoparticles. The objective of this study is to determine whether this aspect can be addressed by a modification of silica particles with gold nanoparticles. Throughout the analysis, we show that after the attachment of gold nanoparticles to silica particles, comparable or better efficiencies to GNOME laser perforation are reached. In combination with 1 µm silica particles, we report laser perforation with gold nanoparticles with sizes down to 4 nm. Therefore, our investigations have great importance for the future research in and the fields of laser transfection combined with plasmonics.